Skill upgrading, wage gap and international trade: Firm-level evidence for Italian manufacturing firms - Irene Iodice; Chiara Tomasi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2015)
This paper aims at investigating the evolution of the employment and wage structure of Italian manufacturing firms in the early 2000s. The work analyzes whether skills and wage movements have been taken place between or within sectors, and within sector, between or within firms. We show that most of the changes are reported within firms and that the rise in the share of skilled workers in the wage bill is due to an increase in the relative demand for skilled labor. The analysis reveals that the relative price of the skilled factor does not adjust positively: the wage premium inside firms indeed falls. The results also suggest that while the relative number of hours worked by skilled workers within firms rises, the hourly wage premium falls. The drop in the hourly wage premium is even larger than that in the annual wage gap. Finally, we observe that the within-firm skill upgrading is strongly and significantly related to trade activities. On the contrary, a firm's change in wage premium is uncorrelated to its level of commitment to international exposure.
Keywords: F16; J21; J24; 330; heterogeneous firms; wage premium; skill upgrading; international trade